The Agenda : Inside the Clinton White House - Woodward, Bob (New York Pocket Books, 1995)
Working behind the scenes for the eighteen months following Bill Clinton's election, conducting hundreds of interviews with administration insiders and other key officials, and gaining access to confidential internal memos, diaries, and meeting notes, Bob Woodward has discovered how the Clinton White House really works. Clinton's pledge for a new economic deal was the cornerstone of his 1992 campaign, and fulfilling it has been his central ambition and enterprise as president. By focusing on Clinton's efforts to pass a comprehensive economic recovery plan, Woodward takes us not only to the highest level meetings, the hard-fought debates, and the most difficult decisions but also to the very heart of this presidency - and of this man. With its day-by-day, often minute-by-minute account, it is one of the most intimate portraits of a sitting president ever published. President Clinton is shown as he debates, scolds, pleads, celebrates, and rages in anger and frustration. What emerges also is a group portrait of Clinton's innermost circle of advisers in action - including his wife, Hillary; Vice President Al Gore; Treasury Secretary Lloyd Bentsen and the economic team; George Stephanopoulos and David Gergen and the White House staff; James Carville, Paul Begala, and the other outside political strategists; Congressional leaders; and Federal Reserve Chairman Alan Greenspan. Using his proven research method - returning time and again to key sources and relying on the paper trail of internal documentation - Woodward has assembled an extensive archive of the early Clinton presidency.
Include Index
Keywords: United States -- Politics and government -- Presidents--Staff